Global environmental law at a crossroads - Percival, Robert V.; Lin, Jolene; Piermattei, William; IUCN Academy of Environmental Law (Cheltenham, UK : Edward Elgar, 2014)
'From 30 June to 5 July 2012, the International Union for Conservation of Nature (IUCN) Academy of Environmental Law held its 10th Annual Colloquium at the University of Maryland Francis King Carey School of Law. The Colloquium was held just a week after the conclusion of the once-a-decade UN Conference on Sustainable Development, also known as the'Rio+20' earth summit. At the Colloquium, 250 environmental law experts from 30 countries on six continents focused on the future of global environmental law in the wake of the Rio+20 gathering. This provided a unique opportunity for top scholars to discuss future directions for global environmental law and policy. The Colloquium theme was broadly designed to stimulate presentations touching on all aspects of environmental law. It spawned more than 150 presentations spanning the full spectrum of topics in this rapidly growing field, as reflected in this publication. This book is organized into three parts: environmental governance frameworks, specific environmental challenges and assessment of various governance models... This book is representative of the wide-ranging presentations at the IUCN Academy of Environmental Law's 10th Colloqium.'--Introduction.
Introduction / Robert V. Percival, Jolene Lin and William Piermattei -- Strengthening national environmental governance to promote sustainable development / Scott Fulton and Steve Wolfson -- The future we want and constitutionally enshrined procedural rights in environmental matters / James R. May and Erin Daly -- The rights of nature in Ecuador : an opportunity to reflect on society, law and environment / Jordi Jaria i Manzano -- Environmental NGOs and sustainable development in China / Yuhong Zhao -- The Middle East: climate change, water insecurity and hydro-diplomacy / Itzchak E. Kornfeld -- Land grabbing and food security in Ethiopia: the dilemmas of sustainable development / Mekete Bekele Tekle -- Protecting gifts from the sea: ocean governance for living marine resources after Rio +20 / Anastasia Telesetsky -- Lost in translation: threatened species law in Australia / Jacqueline Williams, Amanda Kennedy and Donna Craig -- Environmental justice in Nigeria's oil industry: recognizing and embracing contemporary legal developments / Rhuks Ako -- The Clean Development Mechanism and its sustainable development premise: the inadequacy of the Kyoto Protocol to guarantee climate justice / Camille Parrod -- The unbearable tiredness of sustainable development (at different levels, lately) / Nicola Lugaresi -- Cap and trade versus carbon tax to mitigate climate change: a one-size-fits-all solution in China? / Ping Chen and Frank Maes -- Environmental law, policy and governance: environmental management systems for cities / LYE Lin-Heng -- Sustainable management, a sustainable ethic? / Trevor Daya-Winterbottom -- Payment of ecosystem services in Brazil: between efficiency and equity / Ana Maria de Oliveira Nusdeo and Ana Luiza Garcia Campos -- European Union climate law and practice at the end of the Kyoto era: unilateralism, extraterritoriality and the future of global climate change governance / Lorenzo Schiano di Pepe -- Legal challenges in the creation of a world environmental organization / Nils Goeteyn.
Includes bibliographical references and index.
Keywords: Environmental law -- Congresses; Environmental law, International -- Congresses